Severe suppurative otitis media due to Streptococcus pneumoniae serotype 19A in a fully vaccinated infant by age - Saliha Kanik-Yuksek; Belgin Gülhan; Aslınur Özkaya-Parlakay; Tuğba Bedir Demirdağ (Taylor & Francis Group, 2020)
The routine use of pneumococcal conjugated vaccines (PCVs) in childhood has significantly reduced the frequency of invasive pneumococcal diseases (IPDs). Serotype replacement has occurred, resulting in an increase in nonvaccine serotypes. Despite this changing profile, both invasive and noninvasive cases continue to be seen with strains within the scope of PCV coverage. Although older children with comorbid disease are described as a risky group for vaccine insufficiency, vaccine failure patterns should be described in detail.